Improving Students’ Reading Comprehension on Recount Text through Animation Video - Anjeli Grasela; Sada, Clarry; Wardah, Wardah (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This research aims to improve students’ reading comprehension of recount texts through animation videos. This research is classroom action research that was conducted in two cycles. The participants in this research are the students in class VIII C, SMP Negeri 13 Pontianak. The researcher collected the data on students’ improvement in reading comprehension by observing the data through a reading test, an observation checklist, and field notes. The result showed that students’ difficulties in comprehending recount text had been solved by using animation videos as learning media. Animation videos as learning media improved students’ abilities to find the main idea, and specific information, identify references, identify inferences, and the difficult vocabulary of recount texts. Animation videos as learning media improved students’ reading comprehension of recount texts. The students showed improvement in their behavior. During the teaching and learning process in this research, almost all of the students were focused on the researcher and participated actively in class discussions. The students also responded enthusiastically to the class discussions.